THE URGENCY OF THE ROLE OF PARENTS IN SHAPING CHILDREN'S ETHICS (CASE STUDY OF CLASS IV STUDENT MI MIFTAHUL HUDA YOSOMULYO KECAMATAN GAMBIRAN, BANYUWANGI REGENCY) - Uswatun Hasanah (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
In Islamic teachings, children are seen as a trust from Allah to both parents. Therefore, parents have an obligation to protect and educate them so that they are safe in this world and the hereafter. Even the safety of family life is also seen as the responsibility of parents. Many views that it is the obligation and role of parents to work together to educate their children. Optimizing the role of parents in shaping children's character is expected to be able to personalize character values (ethics) and noble character so that they are manifested in a good behavior of child everyday in life. While the real results that can be seen include; love for Allah and His messenger and love for truth, honesty, trustworthiness, responsibility, discipline, respect and courtesy, caring, compassion, kind, humble and tolerant and love peace. This paper aims to describe the urgency of the role of parents in shaping children's character. The discussion of this study uses a qualitative descriptive method and literature study (literature study). The results of this paper are expected that parents should have concepts or provisions in educating their children which include moral or character education, science education, religious education, being fair to children, and giving attention and af ection to children. Parents become role models for their children. Therefore, the role of parents is very important in the development and formation of children's character from an early age.